1978
DOI: 10.1021/jo00419a011
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (.+-.)-ferruginol and (.+-.)-hinokione

Abstract: Stereospecific syntheses of (f )-ferruginol and (f)-hinokione were achieved in which the tricyclic ring system was assembled in the order C -BC -ABC. The key features of the approach involve: (1) the utilization of a lactone bridge as part of an enone protecting group in ring A; (2) the installation of an isopropyl group by the regioselective addition of lithium dimethylcuprate to a cross-conjugated dienone; (3) the elimination of the lactone bridge with concomitant aromatization of ring C; and (4) the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Chart ) as the key synthetic intermediate (Scheme 12). Reductive alkylation, followed by removal of the C(3) carbonyl moiety using a thioketal/reduction sequence, completed the functionalization of the A ring (cf. 69 ).…”
Section: Synthetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chart ) as the key synthetic intermediate (Scheme 12). Reductive alkylation, followed by removal of the C(3) carbonyl moiety using a thioketal/reduction sequence, completed the functionalization of the A ring (cf. 69 ).…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Cyclialkylation of 79 to tricycle 80 occurred in high yield under mild conditions. Watt and co-workers have shown that compound 80 can be converted to hinokione in two steps …”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Hydrogenolysis of (±)-sugiol (62) over 30% Pd/C removed the benzylic ketone and produced (±)-ferruginol (3). 56 The resulting intermediate 296 was then elaborated to introduce the appropriate functionality in the C ring, previous protection of the enone moiety in the A ring. Thus, the ketalisation of compound 296 with ethylene glycol proceeded with concomitant lactonisation to give the bridged δ-lactone 297.…”
Section: Tetrahedron 16mentioning
confidence: 99%
“…Similarly, the acid (11) was subjected to CH 3 SO 3 H-P 2 O 5 promoted domino acylation-cycloalkylation with veratrole (18) to yield the tricyclic ketone (19), which was * To whom the correspondence should be addressed. Fax: (91) (22) 26528547.…”
mentioning
confidence: 99%
“…Acid 11 was then subjected to concentrated H 2 SO 4 promoted domino alkylation-cycloacylation with anisole (12) to yield the tricyclic ketone (22), which was subsequently transformed, as depicted in Scheme 6, to the octahydrophenanthrene (23), which has been previously converted [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] to the antibacterial 16 diterpene, (()-totarol (4).…”
mentioning
confidence: 99%